A Tale of Two O's: Odysseus and Oedipus in the Black Atlantic - Emily Greenwood (NWIG, 2009)
[First paragraphs]
Crossroads in the Black Aegean: Oedipus, Antigone, and Dramas of the African Diaspora. Barbara Goff & Michael Simpson. Oxford: Oxford University Press, 2007. xii + 401 pp. (Cloth US$ 150.00)
Romare Bearden: A Black Odyssey. Robert G. O’Meally. New York: DC Moore Gallery, 2007. 116 pp. (Cloth$ 45.00)

Commenting on cultural imperialism under European colonialism, Frantz Fanon (1990:39) remarked that “The settler makes history; his life is an epoch, an Odyssey.” In Fanon’s analysis the settler’s sense of history derived from the history of the “mother country,” rather than the history of the colony that he or she inhabited. But history did not stop here: the reference to the Odyssey reminds us that behind the modern colonial metropolis was a fictional line of descent reaching back to a Greco-Roman cradle, such that the
European settler could lay claim to an even more ancient cultural inheritance. The two books examined here make short work of these classical imperial fictions; O’Meally demonstrates how Romare Bearden’s collages of the
Odyssey collaborate with Homer, jazz style, to produce an epic that Black America can recognize as its own. If the voyage of Odysseus is sometimes taken to symbolize the migration of ancient Greek civilization toward the West, Barbara Goff and Michael Simpson interject the troubled figure of Oedipus, who plays Poseidon to the settler’s Odyssey, disrupting the voyage and confusing the trajectory (p. 268).
Both studies are timely and speak to a wave of recent research on Black Classicism – an examination of the work to which the classical tradition has been put in Africa and the African diaspora, ranging from the hegemonic appropriation of Classics by colonizers and slave-owners to the use of
Classics as an ironic counterdiscourse that writes back to racism and imperialism, or as a source of mythopoiesis in the formation of modern black identity.